(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This study looks at the problem of emotional weariness among doctors, including its signs and root causes. The study that identified emotional tiredness syndrome in doctors and students from a variety of specialties served as the basis for the essay. The causes, signs, and symptoms of burnout in the medical field. The essay was based on a research that looked at how doctors and students from a range of specialties could Keywords: identify sickness, the doctors, symptom medicine, of and emotional emotional tiredness.